The Crowfield curse - Walsh, Pat, 1954- (New York : Chicken House, 2010)
In 1347, when fourteen-year-old orphan William Paynel, an impoverished servant at Crowfield Abbey, goes into the forest to gather wood and finds a magical creature caught in a trap, he discovers he has the ability to see fays and becomes embroiled in a strange mystery involving Old Magic, a bitter feud, and ancient secrets.
Keywords: Orphans -- Juvenile fiction; Magic -- Juvenile fiction; Secrecy -- Juvenile fiction; Monasteries -- Juvenile fiction; Blessing and cursing -- Juvenile fiction; Great Britain -- History -- 14th century -- Juvenile fiction; Orphans -- Fiction; Magic -- Fiction; Secrets -- Fiction; Monasteries -- Fiction; Blessing and cursing -- Fiction; Great Britain -- History -- 14th century -- Fiction